LONG-TERM SURVIVAL OUTCOMES OF RADIATION THERAPY FOR UNRESECTABLE, LOCALLY ADVANCED NON-SMALL CELL LUNG CANCER: A SINGLE-CENTER EXPERIENCE AT HOSPITAL 175 - Vu Hong , Nam; Nguyen Thanh , Cong; Phan The , Nhat; Ngo Đang , Huong; Ho Thi , Hong; Nguyen Mai , Linh; Truong Vu Manh , Dung; Nguyen Đuc , Cong; Nguyen The , Ngoc; Nguyen Thi Thu , Thao (Tạp chí Y Dược Thực hành 175, 2024)
Objective: To evaluate the effectiveness of radiotherapy on overall survival (OS) and identify factors affecting survival outcomes in patients with stage III non-small cell lung cancer (NSCLC) where surgery is not feasible. Methods: This retrospective study analyzed data from NSCLC patients treated with radiotherapy at Hospital 175 from January 2019 to June 2022. Collected data included patient demographics, pathology, TNM staging, concurrent chemotherapy, PET/CT characteristics, and radiotherapy parameters. Patients received concurrent or sequential chemotherapy with radiotherapy doses equivalent to or exceeding 60Gy, with regular follow-up and re-examination post-radiation to document final patient status. Results: Among 240 patients (75% male), performance status (PS) scores of 0, 1, and 2 were 15%, 80%, and 5%, respectively. Histopathological subtypes included squamous cell carcinoma (9%), adenocarcinoma (83.5%), and others (7.5%). Stage IIIA, IIIB, and IIIC comprised 32%, 48%, and 20% of cases, respectively. The median follow-up was 16.3 months, with a median OS of 19.5 months. OS rates at 1, 2, and 3 years were 76.2%, 38.8%, and 27.4%, respectively. Patients receiving concurrent chemoradiotherapy had better OS compared to those with sequential chemoradiotherapy. Age, histopathological type, and lymph node metastasis significantly impacted overall survival. Conclusion: The study highlights that OS rates at 1, 2, and 3 years were 76.2%, 38.8%, and 27.4%, respectively. Concurrent chemoradiotherapy provided a better prognosis than sequential therapy. Radiotherapy remains a crucial treatment modality for inoperable NSCLC, with concurrent chemoradiotherapy offering the best survival benefits. Prognostic factors for survival included age, lymph node metastasis, and histopathological type.